If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + y + 2xy + 6y + -2x = 0 Reorder the terms: 4x + -2x + 2xy + y + 6y = 0 Combine like terms: 4x + -2x = 2x 2x + 2xy + y + 6y = 0 Combine like terms: y + 6y = 7y 2x + 2xy + 7y = 0 Solving 2x + 2xy + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 2x + 2xy + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 2x + 2xy + 0 = 0 + -7y 2x + 2xy = 0 + -7y Remove the zero: 2x + 2xy = -7y Combine like terms: -7y + 7y = 0 2x + 2xy + 7y = 0 The solution to this equation could not be determined.
| logx(3x-1)=0 | | 7/2=91/x | | 6-y=-y+2 | | (xy)dx=(1+x^2)dy | | 12-6r=2r+36 | | 12-5=x/4 | | 6x-15-x=65 | | 1/5x-9/10x=10-31 | | 10=s-2 | | 7+(3)= | | 9c=50f-160 | | 16x+11=6x+231 | | 29x-34x=7-12 | | (8x+18)+(20x+4)=(6x+4) | | -4n+2=-54 | | x^2+y^2+4x+4y+8=9 | | 48-11=35x+15 | | -39+18=-5x+12x | | 3t(t+4)-3=3t(3t)+9t | | v/3-3=v/2 | | T/54=5/6 | | 3*(2-2x)=-6*(x-1) | | 3x(2-2x)=-6(x-1) | | 6x+34=-36 | | -0.7X+5.85=-0.5X+8.25 | | 4(3x-4)=2(3x+1) | | (20x+4)=(6x+4) | | 10.410= | | 3x(2-2x)=-6x(x-1) | | 2w-54=-w+21 | | 7a+4=4a | | 2=5y-3 |